Impact of Nanofiller Fractions on Selected Properties of Microfilled Composite Resin - Parpo, Enni (My University, 2026)
Objective: To assess the impact of incorporating various weight fractions of nanometer-sized particulate fillers on specific properties of microfilled composite resin. Methods: Microfilled composite resin was prepared by mixing 29 wt.% of resin matrix (BisGMA/TEGDMA) with the 71 wt.% of silane treated particulate fillers (Ø 0.4 µm). Then, various fractions of nanometer-sized (180 nm) fillers (0, 5, 10, 15, 20, 25, 30, 35 wt.%) were added gradually using a high speed mixing machine. For each resin composite, flexural properties (n=8) were evaluated using a three-point bending test on a universal testing machine (ISO standard 4049). Fourier transform infrared (FTIR)-spectrometry was used to calculate the degree of monomer conversion (DC%). Surface microhardess (Vickers) was also determined. Surface gloss was measured before and after polishing (4000-grit paper). A two-body wear test was performed in a ball-on-flat configuration using a chewing simulator with 15000 cycles. A non-contact 3D optical profilometer was utilized to measure wear depth. An analysis of variance (ANOVA) was applied to interpret the results statistically, and then the post hoc Tukey analysis was performed. Results: ANOVA revealed that the fraction of nanofillers had a significant effect (p<0.05) on flexural modulus, DC%, microhardness, gloss and wear depth. The group without nanofillers showed the highest DC% (56.6), gloss after polishing (76.2 GU) and wear resistance (24.2 µm) values. Whereas the group with 35 wt.% of nanofillers had the highest flexural modulus (9 GPa) and microhardness (70 VH). Conclusion: It is beneficial to add nanofillers to microfilled composite resin, however it is essential to assess the proportion ratio carefully. Optimising all the properties of composite resin at once with just one formulation is challenging.